Oxidation behaviour of AM50 magnesium alloy containing lanthanide elements. Issue 6 (5th October 2012) - Arrabal, R.; Pardo, A.; Mohedano, M.; Merino, M. C.; Paucar, K.; Casajús, P.; Matykina, E.
<x xml:space="preserve">Abstract</x> The influence of Nd and Gd additions on the microstructure, hardness and oxidation of AM50 magnesium alloy was investigated. Nd and Gd formed Al2Nd, Al2Gd, AlMnNd and AlMnGd intermetallics and reduced the amount of β‐phase. Grain size and hardness did not change significantly with the addition of Nd or Gd. For all the alloys, surface degradation was negligible at temperatures below 370 °C. However, at 410 °C, severe oxidation was observed and hardness values decreased by ∼30% due to grain coarsening. At this temperature, the modified alloys revealed oxidation rates between ∼2.3 and 20 times smaller than the unmodified alloy.